Language – manifestations of culture - Ф., Орaзaқынқызы; А.К., Анипинa (Journal of Oriental Studies, 2019)
For several centuries, the problem of the connection between culture and language has occupied the minds of many famous scientists, but today this problem still remains debatable: some believe that language refers to culture as part of the whole, some that language is a form of cultural expression, and still others that language is neither an element nor a form of culture. The founder of “language philosophy” ilhelm von Humboldt studied the problem of the relationship of language and culture. Humboldt connects the features of the language with the features of the spiritual life of the people (Vil’gel’m fon Gumbol’dt. 1985). For example, the American linguist E. Sepir believes that “culture can be defined as what this society does and thinks, language is how it thinks.” The issue of culture is associated with a changing attitude towards language. 70s of the twentieth century. were “an attack of semantics”, the 80s – the heyday of a communicative approach to language, the end of the 20th century. – cognitive noise, the 21st century significantly expanded these boundaries of linguistics. The problem of the relationship between culture and language is of great interest to scientists of various fields such as sociologists, philosophers, linguoculturologists, linguists, psychologists, etc. And each culture has its own language system, and with the help of this system its speakers have the ability to communicate with each other, therefore the value language in the culture of any people is difficult to overestimate. According to linguistic practice, language is not a mechanical complement to culture, in which case the potential of the language would be limited to one cultural boundary, the language would not be used in intercultural communication. The property of a language is its universality; a person can use the language in all respects. Key words: culture, language, linguistics, linguoculturology.